INTEGRASI KOMPETENSI DALAM PELATIHAN KEPEMIMPINAN - Ni Ketut Riani (Jurnal Inovasi Penelitian, 2021)
The integration of competence in leadership training in Indonesia is a problem that needs to be appreciated by all parties because during this time there is still opposition in the Ministerial regulation of state control and bureaucratic reform number 38 of 2017 about the competency standards Department of civil apparatus of the state, which is caused by the ego of each executor in the existing ministry. Nevertheless, state administrative institutions have taken the initiative to make changes from the curriculum of education and leadership training of the new pattern of the old regulation of the Head of State Administration Regulation number 18, 19 and 20 of 2015 to new patterns established with the administrative regulations of to the state number 15 and 16 of 2019 which integrate the leadership competence and government competence. There are 7 types of competencies integrated into this new curriculum, which is policy of decentralization, central government relations with local governments, general government, regional financial management, government affairs that become regional authority, local government relations with regional representatives and government ethics. For the success of this competency integration needed improvement in training planner which is design build learning training and training plan by integrating 7 government competencies in Agenda 1 Pancasila leadership and defending the country, agenda 2 leadership serve, agenda 3 control implementation activities and agenda 4 leadership actualization. Through perfecting training leadership subjects as competency units, subject matter as elements of competency and sub-material as performance creteria. From the results of the study to elements of Etics and integrity studies in public service should be trainedt and experienced to supervisors level training as many as 8 work performance creteria.